Discovery of SNPs and InDels in papaya genotypes and its potential for marker assisted selection of fruit quality traits - Dieimes Bohry (Nature Portfolio, 2021)
Abstract Papaya is a tropical and climacteric fruit that is recognized for its nutritional benefits and medicinal applications. Its fruits ripen quickly and show a drastic fruit softening, leading to great post-harvest losses. To overcome this scenario, breeding programs of papaya must invest in exploring the available genetic variation to continue developing superior cultivars with improved fruit quality traits. The objective of this study was to perform a whole-genome genotyping (WGG) of papaya, predict the effects of the identified variants, and develop a list of ripening-related genes (RRGs) with linked variants. The Formosa elite lines of papaya Sekati and JS-12 were submitted to WGG with an Illumina Miseq platform. The effects of variants were predicted using the snpEff program. A total of 28,451 SNPs having Ts/Tv (Transition/Transversion) ratio of 2.45 and 1,982 small insertions/deletions (InDels) were identified. Most variant effects were predicted in non-coding regions, with only 2,104 and 138 effects placed in exons and splice site regions, respectively. A total of 106 RRGs were found to be associated with 460 variants, which may be converted into PCR markers to facilitate genetic mapping and diversity studies and to apply marker-assisted selection (MAS) for specific traits in papaya breeding programs.